Prevalence and co-incidence of geriatric syndromes according to the ECOG performance status in older cancer patients - Topcu, Atakan; Yasin, Ayse Irem; Besiroglu, Mehmet; Sucuoglu Isleyen, Zehra; Alaca Topcu, Zeynep; Simsek, Melih; Turk, Haci Mehmet; Seker, Mesut; Soysal, Pinar (Frontiers in Medicine, 2024)
Background: Geriatric syndromes may be more common in older cancer patients than those without cancer. Geriatric syndromes can cause poor clinical outcomes. Eastern Cooperative Oncology Group Performance Status is often used clinical-reported functional status score in oncology practice. Methods: Our study was designed as a cross-sectional study and included 218 older cancer patients. This study aims to determine the prevalence and relationship of geriatric syndromes according to ECOG performance status in older cancer patients. Results: The mean age was 73.0±5.6 of 218 participants, with 47.7% women and 52.3% men in our study. ECOG-PS 0, 1, and 2 groups contained 51%, 39%, and 10% of patients. The mean number of geriatric syndromes in the ECOG 0, 1, and 2 groups were 2.3±2.2, 4.3±2.4, and 5.7±2.1, respectively (p< 0.001). After adjusting for age and gender, it was determined that dynapenia was 2.9 times, probable sarcopenia 3.5 times, frailty 4.2 times, depression 2.6 times, malnutrition 3.3 times, insomnia 2.2 times, falls 2.5 times, and risk of falling (TUG) was 2.4 times more in those with ECOG-PS 1 compared to those with ECOG-PS 0. Besides, it was found that dynapenia was 6 times, probable sarcopenia 6.8 times, frailty 10.8 times, depression 3.3 times, malnutrition 6.3 times, and risk of falling (Tinnetti Balance) 28 times, and risk of falling (TUG) was 13.6 times more in those with ECOG-PS 2 compared to those with ECOG-PS 0. Conclusion: Our study found that the prevalence of geriatric syndromes increased as ECOG-PS increased. Geriatric syndromes and their co-incidence were common in older cancer patients even in normal performance status. Oncologists should incorporate geriatric syndromes into the decision-making process in cancer treatment to maximize the impact on clinical outcomes in older patients with cancer.